ChatGPT as a Pedagogical Tool: Measuring Its Influence on Cognitive Engagement and Academic Achievement of Biology Students - Jamaluddin, Asham Bin; Bahri, Arsad; Pratiwi, Andi Citra; Lembang, Angela Merici (Jurnal Pendidikan MIPA, 2025)
Abstract: Artificial intelligence technology has been integrated into educational practices and is considered to have a significant influence in improving the teaching and learning process. Biology is one of the science subjects considered as a complex subject and requires deep understanding. The presence of ChatGPT answers the existing problems by offering personalized explanations, interactive feedback, and structured answer recommendations to improve students' understanding and critical thinking. The application of artificial intelligence such as ChatGPT to educational practices has opened up new opportunities to improve learning processes and outcomes. This study explores the effect of using ChatGPT as a pedagogical tool on cognitive engagement and academic achievement of Biology students. This study uses a cross-sectional quantitative survey method with Structural Equation Modeling analysis. The research sample was Biology students consisting of three different batches. The results showed that ChatGPT as a pedagogical tool significantly increased students' cognitive engagement, which then could also mediate its effect on students' academic achievement. In addition, cognitive engagement also has an impact on the formation of Biology students' academic achievement. In general, these findings highlight a good relationship between ChatGPT use, cognitive engagement, and academic achievement, and underline its potential to create a student-centered adaptive learning environment. However, ChatGPT also has some drawbacks, such as over-reliance on technology by students, potential errors in assessment, and inequity related to access to computer devices. This study shows the importance of introducing and using artificial intelligence technology in learning strategies. The results can also provide recommendations for the development of AI in education from a research perspective for educators to make decisions. Further research is needed to explore the relationship in various educational contexts and populations.       Keywords: ChatGPT, cognitive engagement, academic achievement, biology students.